1988
DOI: 10.1017/s0021859600082125
|View full text |Cite
|
Sign up to set email alerts
|

Variation between years in growth and nutrient uptake after anthesis of winter wheat on Broadbalk field at Rothamsted, 1969–84

Abstract: Dry weight, nutrient content and other properties of winter wheat were measured from anthesis to maturity between 1969 . From 1969 the cultivar CapelleDesprez was grown either as a first wheat, in the rotation potatoes, beans, wheat, or as a second wheat, in the rotation fallow, wheat, wheat. From 1979 to 1984 the cv. Flanders was grown in the rotation fallow, potatoes, wheat and in this period the wheat was given fungicide sprays. Grain yield of Cappelle-Desprez grown as a first wheat was greater with 96 than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…However, there appeared to be potential for significant N uptake during grain filling even in crops with high N reserves. Other work on wheat (Woodruff 1972;Cox et al 1985;Thome et al 1988) and sorghum (Muchow 1990) has also indicated a close link between DM and N accumulation. In these studies, an average of 130 g DM was accumulated per g of N taken up.…”
Section: Pre-and Post-anthesis N Uptakementioning
confidence: 83%
“…However, there appeared to be potential for significant N uptake during grain filling even in crops with high N reserves. Other work on wheat (Woodruff 1972;Cox et al 1985;Thome et al 1988) and sorghum (Muchow 1990) has also indicated a close link between DM and N accumulation. In these studies, an average of 130 g DM was accumulated per g of N taken up.…”
Section: Pre-and Post-anthesis N Uptakementioning
confidence: 83%
“…There were, however, big differences in N uptake between 1983 (maximum uptake 19 g/m2), 1984 (26 g/m2; assuming N harvest index of 75%) and 1985 (36 g/m*). Measured uptake in 1983 and 1985 levelled off between the flag leaf stage and anthesis, much earlier than in high-yielding wheat crops at higher latitudes (Spiertz and De Vos 1983;Thorne et al 1988). This occurred even when crops were topdressed in that period, and N should have been readily available in the soil.…”
Section: Nitrogen Uptake and Distributionmentioning
confidence: 91%
“…In addition, excessive pre-anthesis growth in early sowings increased lodging, and as a result yield generally had a negative association with dry weight at anthesis. Even for May sowings, anthesis dry weights were, for example, some 200 g/m2 higher than for high-yielding crops in Western Europe (Spiertz and Ellen 1978;Thorne et al 1988) because continued production during the winter months in Australia more than offset the somewhat lower crop growth rates around anthesis in both g m-2 day-' (21 v. 25) and g/MJ (2.3 v. 3.0). Higher respiration losses and shorter days may have caused these lower crop growth rates.…”
Section: Effects Of Crop Growth On Yieldmentioning
confidence: 95%
“…At the simplest level it can provide a tool to look at or allow for the effects of a single variable. Thorne et al (1988) and Chalabi, Day, Willington & Biscoe (1988) looked at aspects of grain growth in wheat, and associated the process in a simple way with the expected effects of temperature. In the former case it showed the impact of temperature on inter-annual yield variation through effects on grain size in a classical experiment at Rothamsted.…”
Section: Modelling Crop Processesmentioning
confidence: 99%